Think like a marketer : what it really takes to stand out from the crowd, the clutter, and the competition - Sonnier, Lauron (Career Press, 2009)
Do you find marketing to be confusing, difficult, or overwhelming? Are you not sure where to begin? Do you have a plan, but don't know how to make it happen? To act and succeed like a marketer, you must first think like one. When you do, marketing becomes routine, focused, and successful as you take clear, confident steps to grow your business every day. Think Like a Marketer takes the mystery out of marketing. It addresses head-on the principles that must guide every action, decision, and communication that affect your business. In addition, it gives you practical, real-life guidance that you can apply immediately after reading. Chock-full of specific examples and proven processes, Think Like a Marketer will teach and show you how to: -Think, act, and communicate like a marketing pro.-Identify and capitalize on the marketing opportunities that abound in your business every day (but are usually missed).-Stand out in a cluttered and overcrowded marketplace.-"Stir the pot" to build and maintain marketing momentum.-Devise a practical marketing strategy that will show positive results, even on a bare-bones budget. With Think Like a Marketer, you'll be prepared to put marketing into action and turn yourself and your business into a marketing machine! Lauron Sonnier is president of Sonnier Marketing and Communications, Inc. (Houston, Texas). She has helped countless companies, managers, and entrepreneurs put marketing into action to grow their businesses on a daily basis. A member of the National Speakers Association, Sonnier presents powerful marketing ideas and strategies to audiences throughout the country. She has been featured in numerous local and national publications. She holds a BS in Communciations and spent 20 years in the marketing trenches, working in television, public relations, and advertising. A Cajun from Louisiana, Sonnier couldn't talk if you tied her hands